Impact the Labirin: the board game on the student’s numeracy ability - Putra, Deni Dwi; Pamungkas, Aan Subhan; Nindiasari, Hepsi; Fathurrohman, Maman; Porter, Anne (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
This research aims to improve the numeracy abilities of secondary students after using the Labirin: the board game and students' perceptions of mathematics learning using the game. This empirical study research used a one-group pretest posttest design. The research population is all grade-8 students in one of the Islamic public secondary schools (MTsN) in Serang City. The sample is 76 students from two classes as the experimental class who implemented the game in learning mathematics. The instruments used to collect the data are the numeracy ability tests and students' perception questionnaires. Before use, both instruments are tested for validity and reliability. The findings showed that the students' numeracy abilities improved after implementing the game and helped students to learn mathematics easily, especially in whole numbers and fractions. In addition, the student's understanding is also achieved. The implementation of the game also showed that this learning media helps students learn in the classroom and interest in using the game. It can be concluded that, the Labirin: the board game improved the student’s numeracy ability.